Rhetorical Analysis of Hate Speech: Case Study of Hate Speech Related to Ahok’s Religion Blasphemy Case - Kurnia Arofah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
The discussion about hate speech is not something new. However, recently it becomes phenomenon that widely spoken. As something that naturally comes out as a human nature. Nowadays hate speech tends to be harmful because it is supported by new media such as online media and social media. This research try to discuss about hate speech related to religion blasphemy accusation that drags, Basuki Tjahaya Purnama known as Ahok into jail. This paper used qualitative method and rhetoric analysis to analyze the hate speech in online media news related to Ahok’s case. The results are, hate speech came from content posted in website such as online political opinion and news. From ethos aspect, most of the hate speech neglected the ethos aspect which provides the credibility and trustworthiness of the source.; from the pathos aspect, the author of the news are choosing words that triggered anger and negative emotion from its audience; from the logos aspect, most of the hate speech draws it’s readers to logical fallacy due to the lackness of facts of its conclusion claim. The Hate speech rhetoric neglects the ethos and logos aspects and it mostly rely on pathos aspect to persuade its readers for hating.